Polar Horizons: Images of the Arctic in Accounts of Amundsen’s Polar Aviation Expeditions - Cronin, Marionne (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2010)
Despite the conquest of the poles in the pre-war era, in the interwar years explorers continued to be drawn towards the poles—only now they travelled by air. Historians of exploration have argued that the introduction of this modern technology raised the explorer far above the perils of the polar ice, thereby eliminating the danger and hardship at the core of heroic exploration narratives. In this argument, the use of aircraft marked the end of the age of heroic exploration. Examining the press coverage of Roald Amundsen’s polar flights, however, reveals a more complex picture. Although the use of aircraft introduced tensions into the exploration narrative, particularly with regard to the images of the Arctic landscape deployed in these stories, analyzing these images highlights the ways in which the polar landscape was constructed in order to both renegotiate and rearticulate heroic exploration narratives in the era of polar aviation.